Analysis of the structural relationship emotional regulation, academic procrastination, and academic burnout - Arbin Janu Setiyowati; Indriyana Rachmawati; Bambang Budi Wiyono; Henny Indreswari; Eko Pramudya Laksana (Institute of Advanced Engineering and Science, 2024)
Academic burnout (AB) is a problem that many students are currently facing since the online learning policy was implemented. This research aims to analyze the structural relationship between emotional regulation (ER), academic procrastination (AP), and student AB. This research used ex post facto causal relationship explanatory design. The research subjects were 417 high school students in East Java. The sampling was cluster random sampling technique. The data analysis technique used the Rasch model and structural equation modelling (SEM). The results showed that there was a significant relationship between ER and AP and AB. The implication of findings on the school guidance and counselling program is that the counsellors must pay attention to the factors that contribute to student AB so that counselling services can be designed to prevent student AB.